A method for preparing nanocrystalline magnetic core

By applying a transverse magnetic field during ultrasonic rolling and heat treatment of nanocrystalline materials, the problems of increased coercive force and loss of traditional nanocrystalline magnetic cores are solved, lower losses and higher performance are achieved, and production costs are reduced.

CN114694944BActive Publication Date: 2025-03-25SHANGHAI LINEPRINTING MATERIALS CO LTD

Patent Information

Application Number
CN202210320890.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2025-03-25
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

Traditional amorphous nanocrystals have problems of increased coercivity and loss in applications with high frequency and high saturation current intensity, which is difficult to meet the needs of miniaturization and high performance.

Method used

The nanocrystalline magnetic core is generated by ultrasonic rolling processing on the nanocrystalline material and applying a transverse magnetic field during the heat treatment. The method includes step S1: rolling processing to generate pre-treated nanocrystals, step S2: winding the magnetic ring, and step S3: performing heat treatment in a heat treatment furnace, and applying a transverse magnetic field to reduce coercive force and loss.

Benefits of technology

The nanocrystalline magnetic core is achieved, so that the nanocrystalline magnetic core has lower losses while maintaining good device performance, thereby reducing production costs and facilitating mass production of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114694944B_ABST
    Figure CN114694944B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a nanocrystalline magnetic core, comprising: step S1: rolling a nanocrystalline ribbon to generate pre-treated nanocrystalline; step S2: winding the pre-treated nanocrystalline to generate a magnetic ring; step S3: heat treating the magnetic ring using a heat treatment method to generate the nanocrystalline magnetic core. The beneficial effect of the present invention is that by applying ultrasonic rolling treatment to the nanocrystalline material and applying a transverse magnetic field during the heat treatment process, the overall coercive force and loss of the nanocrystalline magnetic core are lowered, so that the nanocrystalline magnetic core has lower loss while having good device performance, thereby reducing production costs and facilitating mass production of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic core manufacturing, and in particular to a method for preparing a nanocrystalline magnetic core. Background Art

[0002] With the advancement of science and technology, the Internet of Everything and the continuous development of network technology, especially in the 5G era, the development of high-density recording technology, high-power and high-frequency magnetic devices and other fields require devices with high performance, high quality, small size and low cost, which requires the preparation of magnetic devices. Soft magnetic alloys and other metal functional materials continue to improve performance and reduce costs. As a new generation of functional materials, high Bs sub-nanocrystalline soft magnetic alloys have excellent soft magnetic properties compared to conventional amorphous nanocrystals, such as high saturation magnetic induction intensity and high saturation current intensity. Now some of them are used in the fields of wireless charging of electronic wearable devices, transformers, inductors, etc.

[0003] As various devices develop towards high functionality, small size, light weight and low cost, traditional amorphous nanocrystals can no longer meet the needs of miniaturization, high saturation current intensity and high frequency power. As Bs increases, the coercivity and loss of soft magnetic alloys will also increase, which requires changing the magnetic domain through magnetic field heat treatment and ultrasonic rolling process to reduce the loss. Therefore, reducing the coercivity and loss of nanocrystals has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0004] In view of the above problems existing in the prior art, a method for preparing a nanocrystalline magnetic core is now provided.

[0005] The specific technical solutions are as follows:

[0006] A method for preparing a nanocrystalline magnetic core, comprising:

[0007] Step S1: rolling the nanocrystal ribbon to generate pre-treated nanocrystals;

[0008] Step S2: Winding the pretreated nanocrystals to generate magnetic rings;

[0009] Step S3: heat treating the magnetic ring using a heat treatment method to generate the nanocrystalline magnetic core.

[0010] Preferably, the heat treatment method in step S3 includes placing the magnetic ring in a heat treatment furnace for heat treatment.

[0011] The heat treatment method specifically includes:

[0012] Step A1: evacuating the cavity of the heat treatment furnace, and then introducing an inert gas into the cavity;

[0013] Step A2: after the temperature is raised to a starting temperature node, the magnetic ring is placed in the cavity;

[0014] Step A3: gradually raising the temperature to at least one predetermined temperature node, and maintaining it for a period of time until the last predetermined temperature node is reached;

[0015] At the same time, a transverse magnetic field is applied into the cavity;

[0016] Step A4: Cooling down to a cooling temperature node.

[0017] Preferably, the starting temperature node ranges from 200°C to 300°C;

[0018] The predetermined temperature node ranges from 450°C to 600°C;

[0019] The cooling temperature node ranges from 200°C to 300°C.

[0020] Preferably, the time interval maintained in step A3 is between 50 minutes and 180 minutes.

[0021] Preferably, the magnetic field strength of the transverse magnetic field is between 1000A / m and 4000A / m;

[0022] The current intensity of the transverse magnetic field is between 500A and 2000A.

[0023] Preferably, in the step S1, an ultrasonic rolling device is used to roll the nanocrystalline ribbon;

[0024] The ultrasonic rolling device comprises an ultrasonic generator and a roller. The surface of the roller is provided with a protruding structure, and the protruding structure is used to form rolling lines on the surface of the nanocrystalline ribbon.

[0025] Preferably, the protruding structure is in the shape of a square, a triangle, a grid, a rectangle or a regular hexagon when viewed from above.

[0026] Preferably, the power of the ultrasonic generator is between 10W-3000W;

[0027] The frequency of the ultrasonic generator is between 21KHz and 200KHz.

[0028] Preferably, the pressure of the roller is between 10Kg and 180Kg.

[0029] Preferably, the coercive force of the nanocrystalline magnetic core is 2.2A / m-6.2A / m, and the loss Pu under DC conditions is 620Goe-820Goe.

[0030] The above technical solution has the following advantages or beneficial effects: by applying ultrasonic rolling treatment to the nanocrystalline material and applying a transverse magnetic field during the heat treatment process, a lower coercive force and loss of the nanocrystalline magnetic core as a whole are achieved, so that the nanocrystalline magnetic core has lower loss while having good device performance, thereby reducing production costs and facilitating mass production of products. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The embodiments of the present invention will be described more fully with reference to the attached drawings, which are provided for illustration and description only and are not intended to limit the scope of the present invention.

[0032] Figure 1 It is a schematic diagram of the preparation method of the present invention;

[0033] Figure 2 It is a schematic diagram of the heat treatment method of the present invention;

[0034] Figure 3 It is a schematic diagram of the ultrasonic roller pressing device of the present invention;

[0035] Figure 4 Schematic diagram of the rolling pattern of the pre-treated nanocrystal surface in an embodiment of the present invention;

[0036] Figure 5 1 is a top view of a protrusion structure in multiple embodiments of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0040] The present invention comprises:

[0041] A method for preparing a nanocrystalline magnetic core, such as Figure 1 As shown, including:

[0042] Step S1: rolling the nanocrystal ribbon 4 to generate pre-treated nanocrystals;

[0043] Step S2: Winding the pretreated nanocrystals to generate a magnetic ring;

[0044] Step S3: heat-treating the magnetic ring using a heat treatment method to generate a nanocrystalline magnetic core.

[0045] Specifically, in view of the many problems existing in the prior art, the present technical solution provides a preparation method, which eliminates the internal stress in the nanocrystalline material by ultrasonic rolling to reduce the coercivity and loss of the nanocrystalline magnetic core. At the same time, the coercivity and loss of the nanocrystalline magnetic core can be further reduced by applying a transverse magnetic field during the heat treatment process.

[0046] In a preferred embodiment, the heat treatment method in step S3 includes placing the magnetic ring in a heat treatment furnace for heat treatment.

[0047] If Figure 2 As shown, the heat treatment method specifically includes:

[0048] Step A1: evacuating the chamber of the heat treatment furnace, and then introducing an inert gas into the chamber;

[0049] Step A2: After the temperature is raised to a starting temperature node, a magnetic ring is placed in the cavity;

[0050] Step A3: gradually raising the temperature to at least one predetermined temperature node and maintaining it for a period of time until the last predetermined temperature node is reached;

[0051] At the same time, a transverse magnetic field is applied into the cavity;

[0052] Step A4: Cooling down to a cooling temperature node.

[0053] In a preferred embodiment, the starting temperature node ranges from 200°C to 300°C;

[0054] The range of the predetermined temperature nodes is between 450°C and 600°C;

[0055] The cooling temperature node ranges from 200°C to 300°C.

[0056] In a preferred embodiment, the time interval maintained in step A3 is between 50 minutes and 180 minutes.

[0057] In a preferred embodiment, the magnetic field strength of the transverse magnetic field is between 1000A / m and 4000A / m;

[0058] The current intensity of the transverse magnetic field is between 500A and 2000A.

[0059] In a preferred embodiment, in step S1, an ultrasonic rolling device is used to roll the nanocrystalline ribbon 4;

[0060] like Figure 3As shown, the ultrasonic rolling device includes an ultrasonic generator 1 and a roller 2. The surface of the roller 2 is provided with a protruding structure, and the protruding structure is used to form a nanocrystalline ribbon 4 on the surface of the nanocrystalline ribbon 4. Figure 4 The rolled texture shown.

[0061] Specifically, Figure 3 As shown, an ultrasonic generator 1 is provided in the ultrasonic rolling device, which is used to generate ultrasonic waves and act on the roller 2 through a transmission structure 3. The roller 2 and the auxiliary cylinder 5 arranged below the roller 2 jointly roll the nanocrystalline ribbon 4. At the same time, the roller 2 also applies ultrasonic waves to the nanocrystalline ribbon 4 to eliminate the internal stress of the nanocrystalline ribbon 4.

[0062] In a preferred embodiment, Figure 5 As shown, the protruding structure is in the shape of a square, a triangle, a grid, a rectangle or a regular hexagon in a top view.

[0063] In a preferred embodiment, the power of the ultrasonic generator 1 is between 10W and 3000W;

[0064] The frequency of the ultrasonic generator 1 is between 21KHz and 200KHz.

[0065] In a preferred embodiment, the pressure of the roller 2 is between 10Kg and 180Kg.

[0066] In a preferred embodiment, the coercivity of the nanocrystalline magnetic core is 2.2A / m-6.2A / m, and the loss Pu under DC conditions is 620Goe-820Goe. The above data show that the coercivity and loss of the nanocrystalline magnetic core produced by the preparation method are better than those of the prior art.

[0067] The technical solution is further described below based on the above preparation method in combination with examples.

[0068] Embodiment 1: A high Bs nanocrystalline ribbon with a thickness of 20 μm is selected as the nanocrystalline ribbon 4, and the power of the ultrasonic generator 1 is set to 80 W, and the pressure of the roller 2 is set to 50 Kg. The nanocrystalline ribbon 4 is input into the ultrasonic rolling device to generate pre-treated nanocrystalline with rolling textures.

[0069] Subsequently, the pretreated nanocrystals are rolled into a magnetic ring of preset specifications and input into a heat treatment furnace. The cavity of the heat treatment furnace has been pre-evacuated and inert gas has been introduced, and preheated to the starting temperature node. After the magnetic ring is placed, the temperature in the cavity is raised to the first predetermined temperature node, and after the first predetermined temperature node is maintained for 60 minutes, the temperature in the cavity is raised to the second predetermined temperature node, and after the second predetermined temperature node is maintained for 90 minutes, the temperature in the cavity is lowered to the cooling temperature node to cool the magnetic ring and generate a nanocrystalline magnetic core.

[0070] In this embodiment, the starting temperature node is 250°C, the first predetermined temperature node is 490°C, the second predetermined temperature node is 540°C, and the cooling temperature node is 240°C.

[0071] After testing, the coercive force of the nanocrystalline magnetic core prepared in Example 1 is 5.2 A / m, and the loss is 808 Goe.

[0072] Embodiment 2: A high Bs nanocrystalline ribbon with a thickness of 20 μm is selected as the nanocrystalline ribbon 4, and the power of the ultrasonic generator 1 is set to 150 W, and the pressure of the roller 2 is set to 50 Kg. The nanocrystalline ribbon 4 is input into the ultrasonic rolling device to generate pre-treated nanocrystalline with rolling textures.

[0073] Subsequently, the pretreated nanocrystals are rolled into a magnetic ring of preset specifications and input into a heat treatment furnace. The cavity of the heat treatment furnace has been pre-evacuated and inert gas has been introduced, and preheated to the starting temperature node. After the magnetic ring is placed, the temperature in the cavity is raised to the first predetermined temperature node, and after the first predetermined temperature node is maintained for 60 minutes, the temperature in the cavity is raised to the second predetermined temperature node, and after the second predetermined temperature node is maintained for 90 minutes, the temperature in the cavity is lowered to the cooling temperature node to cool the magnetic ring and generate a nanocrystalline magnetic core.

[0074] In this embodiment, the starting temperature node is 250°C, the first predetermined temperature node is 490°C, the second predetermined temperature node is 540°C, and the cooling temperature node is 240°C.

[0075] After testing, the coercive force of the nanocrystalline magnetic core prepared in Example 2 is 3.8 A / m, and the loss is 759 Goe.

[0076] Embodiment 3: A high Bs nanocrystalline ribbon with a thickness of 20 μm is selected as the nanocrystalline ribbon 4, and the power of the ultrasonic generator 1 is set to 150 W, and the pressure of the roller 2 is set to 50 Kg. The nanocrystalline ribbon 4 is input into the ultrasonic rolling device to generate pre-treated nanocrystalline with rolling textures.

[0077] Subsequently, the pretreated nanocrystals are rolled into a magnetic ring of preset specifications and input into a heat treatment furnace. The cavity of the heat treatment furnace has been pre-evacuated and inert gas has been introduced, and preheated to the starting temperature node. After the magnetic ring is placed, a transverse magnetic field is input into the cavity and the temperature in the cavity is raised to the first predetermined temperature node. After the first predetermined temperature node is maintained for 60 minutes, the temperature in the cavity is raised to the second predetermined temperature node. After the second predetermined temperature node is maintained for 90 minutes, the temperature in the cavity is lowered to the cooling temperature node to cool the magnetic ring, and the transverse magnetic field is turned off at the same time to generate a nanocrystalline magnetic core.

[0078] In this embodiment, the starting temperature node is 250° C., the first predetermined temperature node is 490° C., the second predetermined temperature node is 540° C., the cooling temperature node is 240° C., and the magnetic field strength of the transverse magnetic field is 2800 A / m.

[0079] After testing, the coercive force of the nanocrystalline magnetic core prepared in Example 3 was 2.6 A / m, and the loss was 660 Goe.

[0080] Example 4: To illustrate the effect of rolling treatment on reducing the coercive force and loss of nanocrystalline magnetic cores, in this example, a high Bs nanocrystalline ribbon with a thickness of 20 μm is selected and the high Bs nanocrystalline ribbon is directly wound into a magnetic ring of preset specifications.

[0081] Subsequently, the magnetic ring is input into a heat treatment furnace. The cavity of the heat treatment furnace has been pre-evacuated and inert gas has been introduced, and preheated to the starting temperature node. After the magnetic ring is placed, a transverse magnetic field is input into the cavity and the temperature in the cavity is raised to the first predetermined temperature node. After the first predetermined temperature node is maintained for 60 minutes, the temperature in the cavity is raised to the second predetermined temperature node. After the second predetermined temperature node is maintained for 90 minutes, the temperature in the cavity is lowered to the cooling temperature node to cool the magnetic ring, and the transverse magnetic field is turned off at the same time to generate a nanocrystalline magnetic core.

[0082] In this embodiment, the starting temperature node is 250° C., the first predetermined temperature node is 490° C., the second predetermined temperature node is 540° C., the cooling temperature node is 240° C., and the magnetic field strength of the transverse magnetic field is 2800 A / m.

[0083] After testing, the coercive force of the nanocrystalline magnetic core prepared in Example 3 was 4.0 A / m, and the loss was 766 Goe.

[0084] Control group: In order to fully demonstrate that the nanocrystalline magnetic core of the present technical solution has lower coercivity and loss than the prior art, in the control group, only the magnetic ring is heat treated, and the nanocrystalline material is not ultrasonically rolled, or a transverse magnetic field is introduced during the heat treatment process, as follows:

[0085] A high Bs nanocrystalline ribbon with a thickness of 20 μm is selected and directly wound into a magnetic ring with preset specifications.

[0086] Subsequently, the magnetic ring is input into a heat treatment furnace. The cavity of the heat treatment furnace has been pre-evacuated and inert gas has been introduced, and preheated to the starting temperature node. After the magnetic ring is placed, the temperature in the cavity is raised to the first predetermined temperature node. After the first predetermined temperature node is maintained for 60 minutes, the temperature in the cavity is raised to the second predetermined temperature node. After the second predetermined temperature node is maintained for 90 minutes, the temperature in the cavity is lowered to the cooling temperature node to cool the magnetic ring, and the transverse magnetic field is turned off at the same time to generate a nanocrystalline magnetic core.

[0087] In this embodiment, the starting temperature node is 250°C, the first predetermined temperature node is 490°C, the second predetermined temperature node is 540°C, and the cooling temperature node is 240°C.

[0088] After testing, the coercive force of the nanocrystalline magnetic core prepared in Example 3 was 9.0 A / m, and the loss was 1609 Goe.

[0089] The coercivity and loss of the nanocrystalline magnetic cores of Example 1, Example 2, Example 3, Example 4 and the control group were sorted to generate a performance test parameter table under different processing conditions, as shown in Table 1:

[0090]

[0091] Table 1

[0092] The starting temperature node, the first predetermined temperature node, the second predetermined temperature node, the cooling temperature node and the time interval selected in the above-mentioned embodiment 1, embodiment 2, embodiment 3, embodiment 4 and the control group are all the same, and therefore are no longer listed in Table 1.

[0093] By comparing Example 1, Example 2 and the control group, it can be clearly concluded that when no transverse magnetic field is applied during the heat treatment process, the coercive force and loss of the nanocrystalline magnetic core can be effectively reduced by increasing the ultrasonic power.

[0094] Furthermore, by comparing Example 2, Example 3 and Example 4, it can be concluded that:

[0095] 1. By comparing Example 2 and Example 3 under the conditions of the same ultrasonic power and roller pressure, and whether a transverse magnetic field is applied or not, it can be seen that the coercive force and loss of Example 3 are significantly better than those of Example 2, indicating that under the conditions of the same ultrasonic power and roller pressure, the coercive force and loss of the nanocrystalline magnetic core can be further reduced by applying a transverse magnetic field in the heat treatment step.

[0096] 2. At the same time, by comparing Example 2 and Example 4, it can be found that the coercive force and loss of the two are almost the same. It can be seen that the ultrasonic roller pressing device treatment plus conventional heat treatment and the conventional heat treatment plus magnetic field heat treatment almost achieve the same effect of reducing loss and improving performance, and are obviously better than the conventional heat treatment in the comparison column.

[0097] In summary, the high Bs nanocrystal core loss is the lowest when it is subjected to ultrasonic rolling and a transverse magnetic field is applied during the heat treatment process. This indicates that this process changes the direction of the internal magnetic domains in the nanocrystal microscopic world and further releases the internal stress of the nanocrystal material, thereby achieving the purpose of improving the magnetic properties of high Bs nanocrystals and reducing their losses.

[0098] The beneficial effect of the present invention is that by applying ultrasonic rolling treatment to the nanocrystalline material and applying a transverse magnetic field during the heat treatment process, lower coercive force and loss of the nanocrystalline magnetic core as a whole are achieved, so that the nanocrystalline magnetic core has lower loss while having good device performance, thereby reducing production costs and facilitating mass production of products.

[0099] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocrystalline magnetic core, characterized in that: include: Step S1: rolling the nanocrystal ribbon to generate pre-treated nanocrystals; Step S2: Winding the pretreated nanocrystals to generate magnetic rings; Step S3: heat treating the magnetic ring using a heat treatment method to generate the nanocrystalline magnetic core; During the heat treatment process, a transverse magnetic field is also applied to the magnetic ring to change the direction of the internal magnetic domains of the magnetic ring and release the internal stress; In the step S1, an ultrasonic rolling device is used to roll the nanocrystalline ribbon; The ultrasonic rolling device comprises an ultrasonic generator and a roller, the surface of the roller is provided with a convex structure, and the convex structure is used to form rolling lines on the surface of the nanocrystalline ribbon; The ultrasonic power of the ultrasonic rolling is 150W, the rolling pressure is 50Kg, and the magnetic field strength of the transverse magnetic field is 2800A / m; The heat treatment method in step S3 includes placing the magnetic ring in a heat treatment furnace for heat treatment, The heat treatment method specifically includes: Step A1: evacuating the cavity of the heat treatment furnace, and then introducing an inert gas into the cavity; Step A2: after the temperature is raised to a starting temperature node, the magnetic ring is placed in the cavity; Step A3: gradually raising the temperature to at least one predetermined temperature node, and maintaining it for a period of time until the last predetermined temperature node is reached; At the same time, a transverse magnetic field is applied into the cavity; Step A4: cooling to a cooling temperature node; The starting temperature node ranges from 200°C to 300°C; The predetermined temperature nodes include a first predetermined temperature node and a second predetermined temperature node; The first predetermined temperature node is 490° C., and the second predetermined temperature node is 540° C.; The cooling temperature node ranges from 200°C to 300°C.

2. The preparation method according to claim 1, characterized in that: The time interval maintained in step A3 is between 50 minutes and 180 minutes.

3. The preparation method according to claim 1, characterized in that: The current intensity of the transverse magnetic field is between 500A and 2000A.

4. The preparation method according to claim 1, characterized in that: The protruding structure is in the shape of a square, a triangle, a grid, a rectangle or a regular hexagon when viewed from above.

5. The preparation method according to claim 1, characterized in that: The coercive force of the nanocrystalline magnetic core is 2.2A / m-6.2A / m, and the loss Pu under direct current conditions is 620Goe-820Goe.

Citation Information

Patent Citations

  • Coercive-force-enhanced NdFeB thermal deformation magnet as well as preparation method and application thereof

    CN104347217A

  • Magnetic-field heat treatment method of nanocrystal magnetic core

    CN105719826A

  • Processing method of electromagnetic shielding magnetic material

    CN108122669A

Cited By

  • Amorphous nanocrystalline inductance magnetic core and preparation method thereof

    CN115527749A